A telescopic and microscopic examination of acceleration in the June 2015 geomagnetic storm: Magnetospheric Multiscale and Van Allen Probes study of substorm particle injection. Issue 12 (29th June 2016) - Baker, D. N.; Jaynes, A. N.; Turner, D. L.; Nakamura, R.; Schmid, D.; Mauk, B. H.; Cohen, I. J.; Fennell, J. F.; Blake, J. B.; Strangeway, R. J.; Russell, C. T.; Torbert, R. B.; et al.
Abstract: An active storm period in June 2015 showed that particle injection events seen sequentially by the four (Magnetospheric Multiscale) MMS spacecraft subsequently fed the enhancement of the outer radiation belt observed by Van Allen Probes mission sensors. Several episodes of significant southward interplanetary magnetic field along with a period of high solar wind speed ( Vsw  ≳ 500 km/s) on 22 June occurred following strong interplanetary shock wave impacts on the magnetosphere. Key events on 22 June 2015 show that the magnetosphere progressed through a sequence of energy‐loading and stress‐developing states until the entire system suddenly reconfigured at 19:32 UT. Energetic electrons, plasma, and magnetic fields measured by the four MMS spacecraft revealed clear dipolarization front characteristics. It was seen that magnetospheric substorm activity provided a "seed" electron population as observed by MMS particle sensors as multiple injections and related enhancements in electron flux. Key Points: New MMS data show that magnetic reconnection is a fundamental component of relativistic particle acceleration in Earth's magnetosphere The composition and timing of substorm injection fronts that supply radiation belt seed particles can be well resolved using MMS Combined RBSP and MMS data demonstrate that magnetospheric substorms are an essential element in the near‐Earth radiation belt system